The association between body mass index and fibromyalgia severity: data from a cross-sectional survey of 2339 patients. Issue 1 (1st March 2021) - Atzeni, Fabiola; Alciati, Alessandra; Salaffi, Fausto; Di Carlo, Marco; Bazzichi, Laura; Govoni, Marcello; Biasi, Giovanni; Di Franco, Manuela; Mozzani, Flavio; Gremese, Elisa; Dagna, Lorenzo; Batticciotto, Alberto; et al.
Abstract: Objective: Various studies have shown that overweight and obesity are central features of FM, but the real impact of a high BMI on clinical severity in patients with FM is still controversial. The aim of this study was to analyse the relationships between BMI categories and measures of symptom severity and functional impairment using data from a Web-based registry of patients with FM. Methods: Adult patients with an ACR 2010/2011 diagnosis of FM underwent a complete physical examination and laboratory tests and were asked to complete a package of questionnaires covering their sociodemographic and treatment details, in addition to the following disease-specific questionnaires: the revised Fibromyalgia Impact Questionnaire (FIQR), the modified Fibromyalgia Assessment Status questionnaire (ModFAS) and the Polysymptomatic Distress Scale (PDS). Results: A total of 2339 patients were recruited and divided into two weight categories, underweight/normal (U/N, n = 1127, 48.2%) and overweight/obese (O/O, n = 1212, 51.8%). The total and subscales of FIQR, ModFAS and PSD scores were significantly higher in the O/O patients, as were all the mean scores of the individual FIQR items ( P < 0.001 for all). Conclusion: Our findings demonstrate that O/O patients with FM are significantly more impaired than U/N patients in all the symptomatological and functional domains as measured using the FIQR, ModFAS and PDS, thus suggesting that being O/O has an additional effect on symptoms and function.